Before the Petal Falls: A Novella Exploring Self-Efficacy and Learned Helplessness in Young Adults - Petra Teofani Gunawan Hadianto; Dwi Setiawan (Institute of Research and Community Outreach - Petra Christian University, 2024)
This creative thesis is about self-efficacy and learned helplessness in young adults. Self-efficacy is the belief in one’s ability to achieve one’s goal. The lack of self efficacy is known as learned helplessness, a term to describe the belief that one does not have control over the future. Through a novella, this thesis explores why young adults experience lack of self-efficacy and how they develop self-efficacy. This novella implements the theory of self-efficacy by Bandura (1997) and the theory of learned helplessness by Peterson, Maier, and Seligman (1993). The novella tells a story of a young adult girl, Etta, who is living in an oppressive orphanage. Due to her traumatic experience, she suffers from learned helplessness, making her unable to get out of the oppressive environment. However, after reading her senior’s diary, getting support from her close ones, and practicing the skills, she develops the belief that she can escape the orphanage. Her new conviction helps her in overcoming setbacks until she is able to achieve her goal.